Effect of aquatic extracts of oleander and Melia azedarach on the nucleic acid content of trichomonas vaginalis in vivo - Rana Abdullah; Hussain Artain (مجلة التربية والعلم, 2007)
This study was conducted to elucidate the effect of aqueous leaf extract of Nerium oleander and fruit extract of Melia azedarach on nucleic acids content and activity of some enzymes in Trichomonas vagina/is which growth in Diamond's medium tryptone, yeast and maltose (TYM) media. Results indicated that the exposure of T. vagina/is to IC50 concentration of N. oleander leaves and M azedarach fruits extracts showed asignificant decrease in DNA content by 31.5% and 38.2%, respectively, while the RNA content decreased by 28.3% and 50.7%, respectively. Furthermore the totel.l. nucleic acids content decreased by 27.9% and 48.1% , respectively, compared with the untreated trichomonads with plant extracts after 72 hours of growth. The results of this study also indicated that T. vagina/is treated with N. oleander leaves and M azedarach fruits extracts showed inhibed in the activity of thymidine phosphorylase enzyme at rate 32.7% and 69.2% respectively compared with untreated trichomonads with plant extracts after 72 hours of growth. From the results of this study, 1t is obvious that the above mentioned extracts possess an inhibitory effect on nucleic acids and on the activity of the enzyme Thymidine phosphorylase.